FEATURES OF THE CONTENT AND METHODS OF CONDUCTING CLASS WITH STUDENTS OF THE SPECIAL DEPARTMENT OF THE DISCIPLINE “PHYSICAL CULTURE AND SPORT” - I. A. Kabanova; V. A. Seregina; Т. A. Kachalova (Вестник университета)
The changing features of the work of the special organization, taking into account the number of students and differences, associated with the frequent diseases, have been revealed. In the course of research, the percentage of students of the Special Department to the total number of students, entered the State University of Management in the 2018/2019 academic year (12.53 %), has been determined. Four vain groups of diseases have been identified: musculoskeletal system, cardiovascular system, vision, and some students with multiple diseases. In the selection of means and methods of training in physical culture, it is necessary to study in more detail the distribution of students with several diseases among university institutes and reveal study groups in the schedule grid, which require a special teaching approach. The results of this study will serve as the basis of the optimizing medical and prophylactic complexes of exercises for students of the State University of Management.